GIPR Signaling in Immune Cells Maintains Metabolically Beneficial Type 2 Immune Responses in the White Fat From Obese Mice - Efimova, Irina; Steinberg, Inbar; Zvibel, Isabel; Neumann, Anat; Mantelmacher, Dana Fernanda; Drucker, Daniel J.; Fishman, Sigal; Varol, Chen (Frontiers in Immunology, 2021)
Glucose-dependent insulinotropic polypeptide (GIP) communicates information on energy availability from the gut to peripheral tissues. Disruption of its signaling in myeloid immune cells during high-fat-diet (HFD)-induced obesity impairs energy homeostasis, due to the unrestrained metabolically deleterious actions of S100A8/A9 alarmin. White adipose tissue (WAT) type 2 immune cell networks are important for maintaining metabolic and energy homeostasis and limiting obesity-induced inflammation. Nevertheless, the consequences of losing immune cell GIP receptor (GIPR) signaling on type 2 immunity in WAT remains unknown. Bone marrow (BM) chimerism was used to generate mice with GIPR (Gipr-/- BM) and GIPR / S100A8/A9 (Gipr-/-/S100a9-/- BM) deletion in immune cells. These mice were subjected to short (five weeks) and progressive (14 weeks) HFD regimens. GIPR-deficiency was also targeted to myeloid cells by crossing Giprfl/fl mice and Lyz2cre/+ mice (LysMΔGipr). Under both short and progressive HFD regimens, Gipr-/- BM mice exhibited altered expression of key type 2 immune cytokines in the epididymal visceral WAT (epiWAT), but not in subcutaneous inguinal WAT. This was further linked to declined representation of type 2 immune cells in epiWAT, such as group 2 innate lymphoid cells (ILC2), eosinophils and FOXP3+ regulatory T cells (Tregs). Co-deletion of S100A8/A9 in Gipr-/- immune cells reversed the impairment of type 2 cytokine expression in epiWAT, suggesting a mechanistic role for this alarmin in type 2 immune suppression. LysMΔGipr mice on HFD also displayed altered expression of type 2 immune mediators, highlighting that GIPR-deficiency in myeloid immune cells is responsible for the impairment of type 2 immune networks. Finally, abrogated GIPR signaling in immune cells also affected adipocyte fraction cells, inducing their increased production of the beiging interfering cytokine IL-10, and stress- related type 2 cytokine IL-13. Collectively, these findings attribute an important role for GIPR in myeloid immune cells in supporting WAT type 2 immunity.